Pengaruh Penambahan Asam Askorbat Pada Bulu Ayam Sebagai Adsorben Terhadap Kemampuan Adsorpsi Ion Logam Kadmium (Cd2+) Dalam Larutan - Khumairoh, Wilda (Chem Info Journal, 2013)
A study entitled "The Effect of the Addition of Ascorbic Acid as Adsorbents Rooster Feathers Against Metal Ion Adsorption Capability of Cadmium (Cd2 +) in Solution". The research aims to create an adsorbent ascorbic acid modified chicken feathers, chicken feathers characterize adsorbents before and after the modification of ascorbic acid by FTIR and SAA. Application of cadmium metal ion adsorption on conditioned by variations in contact time 20-140 minutes; pH 3-9, and the concentration of 50-300 ppm. Characterization by FTIR spectrophotometer to determine the groups that are on each adsorbent and to measure the average pore surface area and total pore volume were analyzed by SAA. The amount of metal ions adsorbed cadmium was analyzed using AAS, and the determination of adsorption capacity using the Langmuir isotherm equation. The results obtained feather adsorbent before and after the modified ascorbic acid each have a characteristic size of the average pore 1,17779.102 and 3,06246.102 ; adsorbent surface area of 1.211 m2 / g and 1.672 m2 / g, and total pore volume 4,924.10-3 cc / g and 9,269.10-3 cc / g. The best application of cadmium metal ion adsorption by the adsorbent feathers before and after the modified ascorbic acid on contact time of 60 minutes and 40 minutes, with the same pH is 7, and the adsorption capacity of 25.64 mg / g and 26.32 mg / g.